Vitrectomy for Proliferative Diabetic Retinopathy Associated with Klinefelter Syndrome - Tajiri, Kensuke (Case Rep Ophthalmol, 2015)
INTRODUCTION: We encountered a patient with Klinefelter syndrome (KS) who experienced poor outcomes after vitrectomy for proliferative diabetic retinopathy (PDR). CASE: A 44-year-old male with poorly controlled diabetes was diagnosed with KS by chromosome analysis. Ocular findings revealed severe PDR complicated with extensive preretinal hemorrhages and traction retinal detachment in his left eye, and pars plana vitrectomy was subsequently performed for treatment. RESULTS: A clotting hemorrhage developed during surgery and proved difficult to control. Due to postoperative bleeding and redetachment, the vitrectomy was repeated. At the second operation, we performed a silicone oil tamponade; however, the retina was redetached under the silicone oil, and the light perception vision ultimately disappeared. CONCLUSION: The patient, despite showing increased blood coagulability due to diabetes, presented severe coagulopathy, likely related to KS. In patients with KS and severe PDR, the potential difficulty of vitrectomy should always be kept in mind.